Il carteggio fra Roberto Michels e i sindacalisti rivoluzionari The Correspondence between Roberto Michels and the Syndicalists - Giorgio Volpe (Scuola delle Scienze Umane e Sociali. Quaderni)
The book presents the correspondence between Roberto Michels and the Italian and French (Sorel and Lagardelle) syndicalists, which constitutes an essential historiographical source for the reconstruction of the controversial political biography of the sociologist. An introductory essay by Giorgio Volpe provides a critical interpretation of Michels' position within the socialist movement. It reconstructs the background of Michels' correspondences and studies the phases of his political militancy through the analysis of his political articles, sociological studies, autobiographical notes and reports on the Italian and German socialist parties' congresses.